Environmental impacts of panela production in the Pacto parish of the Metropolitan District of Quito (Esferas, 2022)
The parish of Pacto is considered Ecuador"™s capital of panela. Pacto"™s population depends economically on livestock and agriculture, especially sugar cane cultivation. The production of panela from sugarcane juice is the main product of the parish, and a large part of its production is consumed in the country and is also exported to Colombia, France, Italy, and Spain. The production process benefits the population economically; however, some of its actions have an impact on the environment. This sector has technological problems that directly damage the production process, profitability, and economic sustainability. The main environmental problems are related to the impact on surface water and groundwater, terrestrial flora and fauna, and workers' health. The main positive impact is the generation of employment for the sector's population. The need for the population to be able to use their natural resources in a sustainable manner makes knowing the impacts generated by their activities a priority. In this work, the main environmental impacts of panela production were identified, and measures are proposed as part of an environmental management plan to reduce those impacts.
Keywords: sugar cane; bagasse; thermal efficiency; environmental problems